On the evolution of multiple jobholding in Canada - Olena Kostyshyna; Étienne Lalé (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2021)
In Canada, the fraction of workers holding multiple jobs has almost tripled since the mid-1970s. In this paper, we document this historical change and provide a comprehensive account of its dynamics. We use restricted-access panel micro-data from the Canadian labour force survey to construct transition probabilities in and out of multiple jobholding. We analyze these data through the lens of a trend decomposition that separates out the role of worker inflows and outflows. The upward trend in multiple jobholding is chiefly explained by the increased likelihood of single jobholders to pick up second jobs. While economic reasons remain important among the motives that push workers towards multiple jobholding, a more flexible hours schedule in the main job may explain why taking on a second job has become more frequent.
Keywords: E24; J21; J22; J60; 330; Multiple jobholding; Worker flows; Long-run trends; Business cycles